HYPNOTHERAPY FOR CHILD PERPETRATORS IN CRIMINAL ACTS - Ratna Widianing Putri (Cepalo)
In the era of technological advancement, social changes bring forth both opportunities and challenges for children's education, including easy access to harmful content like pornography, violence, bullying, and depictions of murder. Exposure to such material during their formative years can deeply influence a child's subconscious mind, shaping their values and mindsets, potentially leading to the manifestation of criminal behavior later in life. Simply implementing a comprehensive coaching model to modify behavior and thought patterns may not suffice in addressing these deeply ingrained influences. Therefore, this research aims to propose a supplementary approach utilizing hypnotherapy techniques to access the subconscious mind for more effective intervention. The primary objective is to develop a model for guiding Juvenile Offenders of criminal actions, specifically focusing on integrating a hypnotherapy program within existing intervention frameworks, such as LPKA. The methodology involves in-depth interviews with relevant informants and a comprehensive literature review encompassing primary and secondary sources, including legal decisions, academic journals, books, previous research studies, and relevant articles. The theoretical frameworks utilized for analysis include the well-established concepts of the differential association theory, which examines how individuals learn deviant behavior through social interactions, and coaching theory.